Analisis Pengaruh Tingkat Bunga, Tingkat Inflasi, Earning Per Share Terhadap Harga Saham PT. Bank Mandiri (persero) Tbk. - Didi Rahmat (STIE 'INDONESIA' Pontianak, 2013)
In this research, we investigate impact of Inflation Rate, Interes Rate and Earning per Share as independent variable to the PT. Bank Mandiri (persero) Tbk. stock price. We use causality research with multiple regression analysis method to answer the hypothesis. As conclusion that find, all independent variabel have impact significantly to the stock price in 0.78%. In partial, inflation has no impact to the stock price. In other way, interest rate have significantly influence to the stock price. But the influence is negative. EPS fositive have influence significantly to stock price.